1991
DOI: 10.1080/08927019109378176
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of commercially available mouthrinses on the development of plaque, gingivitis and enamel surface free energy

Abstract: In this study the clinical effects of 6 commercially available mouthrinses on the development of plaque and gingivitis and on the tooth surface free energy were evaluated in vivo. The following rinses were used: Hibident ® (containing 0-2% chlorhexidine), Prodent ® (containing 005% sodium fluoride) Meridol ® (containing 125 ppm aminefluoride, 125 ppm stannous fluoride), Merocet ® (containing 0.05% cetylpyridinium chloride), Veadent ® (containing 0.03% sanguinarine) and Listerine ® (containing several phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…[24] AF adsorption to salivary pellicles has been extensively studied in the past[25] with respect to its effects on the charge and hydrophobicity of pellicle surfaces, but never with respect to its effects on tooth surfaces in vivo , as can be established through intraoral contact angles measurements. [26] Recent studies have shown that the hydrophobicity of tooth surfaces goes through a daily cycle, becoming hydrophilic after brushing and recovering to relatively hydrophobic values during the day, depending on the type of toothpaste employed. [27] Interestingly, in vitro water contact angles on toothpaste-treated and untreated pellicle surfaces were generally more hydrophilic than those observed in vivo , likely because in vivo greasy substances adsorbed from food and initial biofilm formation form part of the pellicle.…”
Section: Discussionmentioning
confidence: 99%
“…[24] AF adsorption to salivary pellicles has been extensively studied in the past[25] with respect to its effects on the charge and hydrophobicity of pellicle surfaces, but never with respect to its effects on tooth surfaces in vivo , as can be established through intraoral contact angles measurements. [26] Recent studies have shown that the hydrophobicity of tooth surfaces goes through a daily cycle, becoming hydrophilic after brushing and recovering to relatively hydrophobic values during the day, depending on the type of toothpaste employed. [27] Interestingly, in vitro water contact angles on toothpaste-treated and untreated pellicle surfaces were generally more hydrophilic than those observed in vivo , likely because in vivo greasy substances adsorbed from food and initial biofilm formation form part of the pellicle.…”
Section: Discussionmentioning
confidence: 99%
“…After a minimum period of at least 1 week, in vivo water contact angles were measured on the teeth from enlarged photographs, taken with a camera especially designed for intraoral use [Perdok et al, 1991]. Contact angles were measured on 2 different days in a week and this was repeated twice.…”
Section: Water Contact Angles In Vitro and In Vivomentioning
confidence: 99%
“…Because of its cationic nature, AmF are also expected to interact with negatively charged bacterial cell surfaces as well as with salivary pellicle surfaces through electrostatic interactions [Shani et al, 1996]. AmF adsorption to salivary pellicles has been extensively studied in the past [De Jong et al, 1984;Shani et al, 1998] with respect to its effects on the charge and hydrophobicity of pellicle surfaces, but never with respect to its effects on tooth surfaces in vivo, as can be established through intraoral contact angles measurements [Perdok et al, 1991]. Recent studies have shown that the hydrophobicity of tooth surfaces goes through a daily cycle, becoming hydrophilic after brushing and recovering to relatively hydrophobic values during the day, depending on the type of toothpaste employed .…”
mentioning
confidence: 99%
“…Research in various laboratories has suggested significant differences in conditioning film development under controlled laboratory or in vivo conditions and within typical patient experience (2, 3). de J ong et al .…”
mentioning
confidence: 99%
“…Studies with reconstituted human whole saliva (RHWS) showed reductions in water contact angles on enamel during pellicle formation to 30–35°. Interestingly, intraoral contact angles on the front incisors of human volunteers showed that the pellicle‐coated enamel surface under clinical conditions is considerably more hydrophobic and water contact angles of around 56° have been published for a group of 60 volunteers (3). It is possible that the increased hydrophobicity of in vivo pellicles is a result of adsorption of dietary and dentifrice components from saliva, and in vivo pellicles must be thought of as a film of adsorbed salivary, dietary and dentifrice components.…”
mentioning
confidence: 99%